2021
DOI: 10.1155/2021/5534946
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NQO1 Polymorphisms on Warfarin Maintenance Dose: A Systematic Review and Meta-Analysis (rs1800566 and rs10517)

Abstract: This meta-analysis was conducted to analyze the effect of NQO1 polymorphism on the warfarin maintenance dosage. Using strict inclusion and exclusion criteria, we searched PubMed, EMBASE, and the Cochrane Library for eligible studies published prior to July 7, 2021. The required data were extracted, and experts were consulted when necessary. Review Manager Version 5.4 software was used to analyze the relationship between NQO1 polymorphisms and the warfarin maintenance dosage. Four articles involving 757 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The frequency of the NQO1 rs1800566 T/T genotype is 4% to 20%, depending on the ethnic group, with the highest prevalence in Asian populations (Kelsey et al., 1997 ), especially in Japan. NQO1 rs10517, like the NQO1 rs1800566 polymorphism, affects warfarin metabolism by affecting NQO1 function (Tian et al., 2021 ). NQO1 rs689452 is an intronic polymorphism located in a protein‐binding motif with the potential to modulate NQO1 protein activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of the NQO1 rs1800566 T/T genotype is 4% to 20%, depending on the ethnic group, with the highest prevalence in Asian populations (Kelsey et al., 1997 ), especially in Japan. NQO1 rs10517, like the NQO1 rs1800566 polymorphism, affects warfarin metabolism by affecting NQO1 function (Tian et al., 2021 ). NQO1 rs689452 is an intronic polymorphism located in a protein‐binding motif with the potential to modulate NQO1 protein activity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the NQO1 rs1800566 polymorphism (c.559C>T, p. Pro187Ser) (Lienhart et al., 2014 ), which is common in the Japanese population (Table 1 ), may be associated with the development of SMON. In this study, we analyzed the NQO1 rs1800566 polymorphism and other previously reported loss‐of‐function polymorphisms in NQO1 , rs10517 (c.*1119 T>C; 3′ UTR variant) (Tian et al., 2021 ), rs689452 (c.8‐27G>C; intron variant) (Hemissi et al., 2021 ), and rs689456 (c.‐1221G>A; upstream transcript variant) (Reddy et al., 2009 ), using genomic data for patients with SMON.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, closely-related NQO1, that uses NADH, a typical co-substrate for oxidoreduction reaction, is at least ten times more studied with regard to polymorphic variants than NQO2. Recent systemic reviews confirm that NQO1 PGx is much more advanced compared to NQO2 PGx and addresses specific topics [113][114][115]. We can expect that a better grasp of the regulatory mechanisms of NQO2 enzymatic activity would trigger a stronger interest and faster progress in our understanding of NQO2 genetics, biology and pharmacology in the future.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…These reviews assessed patients receiving OACs for any condition, including cardiomyopathy, heart-valve replacement, and rheumatic heart disease, as well as AF or VTE (see Additional file 4 for details). The update searches identified seven reviews [36][37][38][39][40][41][42] that met the inclusion criteria (see Additional file 4 for details). One [38] of these reported data for patients with AF.…”
Section: Genotypingmentioning
confidence: 99%